2018
DOI: 10.1108/jpbm-05-2016-1194
|View full text |Cite
|
Sign up to set email alerts
|

CSR and corporate branding effect on brand loyalty: a study on Indian banking industry

Abstract: Purpose The study aims to examine the effect of corporate social responsibility (CSR) on corporate branding (CB) and brand loyalty (BL) in the Indian Banking industry. The study further intends to examine the direct and indirect effect of CSR on BL when CSR becomes an integral part of CB. Design/methodology/approach A structured questionnaire using seven-point Likert’s scale is the instrument for data collection. Stratified random sampling is used to collect the cross-sectional data from 430 savings bank cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 176 publications
(279 reference statements)
10
80
0
1
Order By: Relevance
“…It leverages the power of not only a particular company's performance, local economy, and community but also entire economies, countries, and nations in relation to global brands (Kucharska et al, 2018). Pratihari and Uzma (2018) identified a positive relationship between CSR, corporate branding, and brand loyalty. Torres, Bijmolt, Tribo, and Verhoef (2012) found that CSR towards various stakeholders (customers, shareholders, employees, suppliers, and communities) has a positive effect on global brand equity.…”
Section: Brand Performancementioning
confidence: 99%
“…It leverages the power of not only a particular company's performance, local economy, and community but also entire economies, countries, and nations in relation to global brands (Kucharska et al, 2018). Pratihari and Uzma (2018) identified a positive relationship between CSR, corporate branding, and brand loyalty. Torres, Bijmolt, Tribo, and Verhoef (2012) found that CSR towards various stakeholders (customers, shareholders, employees, suppliers, and communities) has a positive effect on global brand equity.…”
Section: Brand Performancementioning
confidence: 99%
“…Meskipun CSR penting dalam semua bidang industri, namun CSR tampaknya sering digunakan oleh sektor perbankan (Balmer, 2017;Pratihari and Uzma, 2018). Beberapa penelitian telah menguji peran CSR terhadap Corporate Image pada industri perbankan (Wang et al, 2015;Bednarska-Olejniczak, 2016;Al Mubarak, Hamed dan Al Mubarak, 2019).…”
Section: Pendahuluanunclassified
“…This character of homogenization makes it challenging for banking marketers to differentiate their product or services from the competitors meaningfully; hence, it poses a serious challenge of how to improve consumer loyalty in an industry that already has very little to differentiate. Second, most of the prior studies in the banking sector have primarily explored the phenomenon of CSR with a philanthropic mindset [19][20][21], whereas the marketing-related perspective in this connection has been largely ignored. The present study aims to bridge these gaps by investigating the dimensional (economic, social, and environmental) impact of the banking sector's CSR initiatives on consumer loyalty.…”
Section: Introductionmentioning
confidence: 99%